Editorial - Forte, Sérgio Henrique Arruda Cavalcante (2016)
In this second issue of the year 2016, the RCA presents 12 articles with the following characteristics: With regard to epistemology, there are eleven positivist studies and one critical study. With regard to the field of study, eleven studies are about administration and one is about economics. With regard to the thematic areas, there are five studies on marketing, two on general administration, two on human resources, one on strategy, one on innovation and one on agriculture. With regard to the theoretical background, the studies are divided into the following backgrounds: four studies on consumer behavior, one study on a brand, one bibliometric study of general administration, one on strategic competence, one on strategic practice, one on risk management, one on social theory, one on innovation and one on trade blocs. With regard to the geographical scope, eight studies are conducted with Brazilian organizations, one with international organizational, one with regional organizations and two with organizations in general. With regard to the sector, nine studies are about the private sector, one is about the public sector and two are about the sectors in general. With regard to the empirical object, there are six studies on trade and services, four studies on general issues, one industry study and one governmental study. With regard to the type of research, there are eleven theoretical and empirical studies and one essay. With regard to the research approach, seven studies are qualitative and five are quantitative. With regard to the language, all the 12 studies are in Portuguese. With regard to the home institutions, all the 12 studies are from national HEIs. With regard to the format, eleven studies use the ABNT style and one uses the APA style. In short, the studies presented here are mostly: positivists; on administration; on marketing, with a focus on onsumer behavior; conducted with Brazilian organizations of the private sector of trade and services; theoretical and empirical studies; using qualitative and quantitative methodological approaches, with a slight predominance of the first one; written in Portuguese; conducted by researchers from Brazilian education institutions in the ABNT style format. In general, in the year 2016, there was a predominance of studies on strategy and marketing themes and a slight predominance of quantitative studies (14 out of 24 studies) in the Journal of Administrative Sciences.